2018
DOI: 10.3389/fmicb.2018.00894
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microbial Composition of Cambodian Traditional Dried Starters (Dombea) on Flavor Compounds of Rice Wine: Combining Amplicon Sequencing With HP-SPME-GCMS

Abstract: Dombae is a traditional ferment starter which has been used for starchy based wine production in Cambodia. However, the production technology of rice wine in Cambodia is not optimized. The current study aimed to investigate the microbiota associated in five ferment starters and the effect of a traditional fermentation process using a metagenomics sequencing analysis and HS-SPME-GCMS for the characterization of the aromatic profiles at the end of fermentation. Most of bacteria identified in this study were lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…Malic acid, the second dominant organic acid, has been reported to be related to yeast and Aspergillus (Peleg et al, 1988;Pines et al, 1996), but no relationship was found between them. However, our study suggested that Weissella and Wolbachia were correlated significantly with malic acid, in which Weissella was identified as one of the dominant LAB in Dombea, a Cambodian traditional stater (Sokny et al, 2018). But its abundance begins to decrease after 2 days in two samples.…”
Section: Discussionmentioning
confidence: 61%
“…Malic acid, the second dominant organic acid, has been reported to be related to yeast and Aspergillus (Peleg et al, 1988;Pines et al, 1996), but no relationship was found between them. However, our study suggested that Weissella and Wolbachia were correlated significantly with malic acid, in which Weissella was identified as one of the dominant LAB in Dombea, a Cambodian traditional stater (Sokny et al, 2018). But its abundance begins to decrease after 2 days in two samples.…”
Section: Discussionmentioning
confidence: 61%
“…Ethnic people practicing the age-old traditional preservation or sub-culturing amylolytic and alcohol-producing as well as flavor-enhancing fungi and bacteria have attracted many researchers to study the microbial diversity in such starters. In recent years, few researchers have reported the fungal and bacterial species using both culture-dependent and-independent techniques in some common starter cultures of Asia such as marcha of India ( Tsuyoshi et al, 2005 ; Sha et al, 2017 ), daqua of China ( Wang et al, 2008 ; Zheng et al, 2012 ; Lv et al, 2013 ; Chen et al, 2014 ; Xu et al, 2017 ), benh men of Vietnam ( Dung et al, 2007 ; Thanh et al, 2008 ); nuruk of Korea ( Jung et al, 2012 ), and dombea of Cambodia ( Ly et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolite production can indeed be considerably modified by the microbial composition [37,38]. Based on the results competitive interaction [13]. The different combination of these three strains has somehow different impacts on chemical compositions of rice wine including lactic acid, acetic acid, and ethanol yield.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, microbial composition has a strong impact on both rice wine quality and yield. Basically, a spontaneous cereal-based fermentation involves complex interkingdom microbial consortia including fungi, yeasts, lactic acid bacteria [2,13]. R. oryzae has been reported as a strong amylase enzyme producer, frequently found in amylolytic ferment starters for rice wine and during saccharification [4,7,9,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation